Development of Plantago coronopus L. individuals in the marginal population and hydroponic culture - Sotek, Zofia (Biodiversity: Research and Conservation, 2006)
Plantago coronopus is a Mediterranean-Atlantic species reaching in Poland the eastern limit of its range. The plant is receding from the area of Poland and at present it is known from only one locality on the Karsiborska Kępa island. The population growing at this locality was studied in the years 1987-1992. The aim of the study reported in this paper was: (i) to compare development of P. coronopus individuals in the natural conditions and in a hydroponic culture, (ii) to find out whether individuals with different life history were concentrated over a certain area or their distribution was random. In the marginal population of P. coronopus on the Karsiborska Kępa island by far dominant was the group of perennial plants; there were much fewer biennial plants and only a few annuals. In general, the plants with different life history were rather randomly distributed. The annual plants were, however, mainly found in the disturbed or recolonised areas. The development of P. coronopus individuals was the fastest in the hydroponic culture conditions, especially the early developmental phases were shortened. Relative to the individuals growing in the natural conditions, those from hydroponic culture earlier produced sister rosettes.